ESENSI HIKMAH SYARI’AH TERHADAP KESETARAAN GENDER - AHMAD MUSYAHID (LPPM IAIN Parepare, 2014)
Gender Issue becomes the warm topic conversed latterly, especially concerning social function and role between men and women. As an universal religion, Islam confess and push the equality of the social function and role. Equivalence gender between men and woman in Islam contain the values ilahiyah to mankind importance. The essential Values of that's recognized by hikmah which is highest at the opposite of existence of equivalence gender.